Design of portable 3-axis filament winding machine with inexpensive control system - Quanjin, Ma; M. R. M., Rejab; Idris, Mat Sahat; M., Amiruddin; Bachtiar, Dandi; Siregar, J. P.; M. I., Ibrahim (Faculty Mechanical Engineering, UMP, 2018)
Filament winding technology is one of the fundamental fabrication methods in composite material fields, which has a high degree of automation. It is the process in which continuous strands or filament of fibres is wound on the mandrel, which is suitable for high-pressure vessels, pipes, shaft and ducts. The present filament winding machines have existed in enterprises or factories, which are high costs, heavy, complex control system and machine structure. The objective of this study is to design a 3-axis filament winding machine, which has portable, lightweight, low costs, high efficient and inexpensive control system features compared to the previous and present machine. The control system relates hardware section and software section, which can meet three axes movement principle. The 3-axis prototype filament winding machine has also been developed. Arduino Uno and CNC v1 shield module are applied as hardware section. Universal G-Code Sender (UGS) and Grbl codes are adopted as software section. In conclusion, a 3-axis portable, lightweight and low-cost filament winding machine have been successfully developed, which can fabricate filament wound carbon/epoxy tubes with a proper inexpensive control system.